PERPUSTAKAAN DIGITAL “ISU PRESERVASI DIGITAL” Alasan, Proses dan Tantangan Ke depan - Sumarni Sumarni; Lailatur Rahmi (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2018)
Preservation of traditional materials became more successful and systematic after libraries and archives integrated preservation into overall planning and resource allocation. Digital preservation is largely experimental and replete with the risks associated with untested Digital preservation strategies are shaped by the needs and constraints of repositories with little consideration for the requirements of current and future users of digital scholarly resources. Archives contain millions of documents like manuscripts, rare books, paintings, photographs, and historical records. All these constitute human heritage. Paper manuscripts, with the passage of time, are getting fragile and brittle because of various reasons. Lamination does not seem to be a permanent solution of preservation this cultural heritage for posterity. Digitization technology brings with it untold benefits for heritage preservation access. Once a document has been properly digitized, it become immortal and can remain accessible long after the original has ceased to exist. The option of digital access further aids in preservation of originals through reduced need for physical handling. This paper states about need for digital preservation with its objectives in Library environment.